Godina's Principles in the Twenty-First Century and the Evolution of Lower Extremity Trauma Reconstruction - Colen, David L.; Colen, Lawrence B.; Levin, L. Scott; Kovach, Stephen J. (Journal of Reconstructive Microsurgery, 2018)
Background February of 2016 marked 30 years since the passing of Marko Godina, a pioneer and prodigy in the field of reconstructive microsurgery. Most noteworthy among his many contributions was his method of radical debridement of contaminated compound fractures followed by early free tissue transfer for wound closure. In the last three decades, the landscape of reconstructive surgery has undergone significant transformation owing to advances in reconstructive techniques and wound care technology, as well as new data.Methods Dr. Godina's work and legacy are reviewed, compared and contrasted with new and evolving data regarding lower extremity trauma reconstruction.Results Advancements in technique and technology have greatly molded lower extremtiy reconstruction over the past thirty years. Nonetheless, Dr. Godina's principles of timely care and early vascularized soft tissue coverage have withstood the test of time.Conclusion Marko Godina's contribution to reconstructive microsurgery cannot be overstated and his groundbreaking work continues to serve as the foundation of lower extremity trauma reconstruction. Three decades after his seminal work, we honor Dr. Godina's legacy and explore how his principles have endured, evolved, or been replaced.
Keywords: Godina; lower extremity trauma; free flap; microsurgery; limb salvage